Identifying expansive learning opportunities to foster a more sustainable food economy: a case study of Rhodes University dining halls - Agbedahin, Adesuwa Vanessa (Rhodes University, Faculty of Education, Department of Education, 2012)
This is a one year half thesis. This research was conducted within the context of the food services sector of Higher Education Institution dining halls and in the midst of the rising global call for food resource management and food waste reduction. The main aim of this research therefore was to identify opportunities for learning and change for a more sustainable food economy, contributing to Education for Sustainable Production and Consumption, and by further implication, Education for Sustainable Development. To achieve this aim, I used Cultural Historical Activity Theory as theoretical and methodological framework; drawing on the second and the third generations of this theory. Implicated in the above research approach is the identification of expansive learning opportunities from the surfacing of 'tensions' and 'contradictions'. In this case study of the Rhodes University Campus Food Services, such tensions and contradictions inhibiting a more sustainable food economy, involving food waste production were identified. To narrow the scope of the study, one dining hall formed the focus of the case, with a two phased research approach whereby one research question and three goals were developed for each phase. The former being the exploration phase and the latter being the initial stages of the expansive phase. Methods used in line with the methodological framework included ten individual interviews with food producers (staff members), nine focus group discussions with food consumers (students), observations of the dining hall activities which lasted for over a month and two 'Change Laboratory Workshops'. Some of the findings of this research are that food wastage cannot be addressed and appropriately curtailed without an intensive consideration of all the stages of food economy. Multiple contradictions and sources of tensions embedded in the Food Services Sector constituted major causes of food waste. Additionally, the lack of substantial food waste related teaching and learning activities, the presence of disputed rules, institutional structure and traditional practices within the Food Services all exacerbated the tensions and contradictions. More so, prioritizing some of this identified contradictions and tensions hindering a more sustainable food economy and relegating some as unimportant or nonurgent is unproductive. Finally, the non-existence of facilitated deliberation, consultation, dialogue, collaboration between food producers and food consumers has been identified as an obstacle to learning and institutional change. Recommendations abound in re-orienting, re-educating, and re-informing the constituents of the food economy. Re-visiting and revising of rules and regulations guiding conduct of students and kitchen staff members in the RU dining halls, as well as revision of existing learning support materials and mediating tools in use is needed. Recognition and consideration of the concerns and interests of students and kitchen staff members are also needed. Finally, there is a need to continue to address the tensions and contradictions identified in this case study, to further the Expansive Learning Process if a more sustainable food economy at Rhodes University is to be established.
Keywords: Food supply -- Education (Higher) -- South Africa -- Case studies; Food industry and trade -- Education (Higher) -- Standards -- South Africa -- Case studies; Food service employees -- Education (Higher) -- South Africa -- Case studies